2018
DOI: 10.20448/2002.21.1.6
|View full text |Cite
|
Sign up to set email alerts
|

CPEC: Pakistan-China Cordial Ties - A Boost to Pakistan's Economy

Abstract: This paper highlights the need of energy production in Pakistan and to determine the extent to which China Pakistan Economic Corridor (CPEC) and its energy projects will contribute to the economic growth and development of Pakistan. In this regard, a fair amount of literature has been reviewed. The literature review presented confirms that a positive relationship exists between the energy production, security and economic development. The long term friendship of Pakistan and China is discussed and how this tie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 10 publications
(10 reference statements)
2
19
0
Order By: Relevance
“…CPEC is the name of several infrastructures, economic development, industrial zones, and regional connectivity projects that are presently under construction throughout Pakistan (Ahmad & Hong, ). Past scholars and policymakers have demonstrated that the CPEC project decreases unemployment by generating millions of employment opportunities (Ali & Qazi, ; Chen et al, ), brings in new business and provides new investment opportunities (Raza, ; Wajeeh & Yang, ), provides opportunities for large‐scale business and small businesses (Rehman et al, ), and generates revenue for host communities (Raza et al, ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…CPEC is the name of several infrastructures, economic development, industrial zones, and regional connectivity projects that are presently under construction throughout Pakistan (Ahmad & Hong, ). Past scholars and policymakers have demonstrated that the CPEC project decreases unemployment by generating millions of employment opportunities (Ali & Qazi, ; Chen et al, ), brings in new business and provides new investment opportunities (Raza, ; Wajeeh & Yang, ), provides opportunities for large‐scale business and small businesses (Rehman et al, ), and generates revenue for host communities (Raza et al, ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…First, energy crisis is among the major problems of Pakistan, which reduces the business opportunities for local and foreign investors (Ali, Rasheed, Muhammad, & Yousaf, ). Pakistan is facing a shortage of electricity since the last decade, and due to power outages and blackouts that frequently occur, businesses suffer heavily (Raza et al, ). To overcome the electricity problem, the energy projects play a vital importance in the CPEC projects.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations